Innovating Taiwan's greenhouse gas estimation: A case study of atmospheric methane using GeoAI-Based ensemble mixed spatial prediction model - Hao-Ting Chang; Yinq-Rong Chern; Aji Kusumaning Asri; Wan-Yu Liu; Chin-Yu Hsu; Ta-Chih Hsiao; Kai Hsien Chi; Shih-Chun Candice Lung; Chih-Da Wu (Journal of Environmental Management, 2025)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Ultrasonography-Based Qualitative and Quantitative Evaluation Approaches for Pompe Disease - Yueh-Hui Lee; Hong-Jen Chiou; Da-Tian Bau; Dau-Ming Niu; Ting-Rong Hsu; Hsuan-En Huang; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to propose the qualitative and quantitative approaches to evaluate the skeletal muscle ultrasound images of 23 Pompe disease (i.e., acid maltase deficiency, AMD) patients and 14 normal subjects. Methods A cohort of 23 AMD patients and 14 normal subjects has been investigated. We compared the B-mode echo intensity of the rectus femoris muscle with that of its surrounding fat (subcutaneous fat) and proposed a qualitative grading method. Quantitative analysis of the region of interest (ROI) with the echo intensity and the segmented area was also performed. Results Qualitative results showed that AMD patients without clinical symptoms (without undergoing ERT) had the highest distribution of Grade 1, and AMD patients undergoing ERT had the widest distribution of Grade 2, and control group (n = 14) with the highest distribution of Grade 1. Using the segmented area approach, quantitative results showed that AMD patients undergoing ERT had the largest and widest distribution. Meanwhile the control subjects (normal subjects) had the lowest and the narrowest areas. The echo intensity of the segmented ROI of AMD patients undergoing ERT displayed the highest and widest (inhomogeneous) distributions. By contrast, the echo intensity of AMD patients without clinical symptoms was slightly increased and with low inhomogeneity. Conclusion The proposed ultrasonography-based qualitative and quantitative approach may be used to evaluate the severity of muscle destruction for AMD patients. Besides, the quantitative segmented area with regression analysis could help predict the incidence of onset of Pompe disease patients.

Unexpected dose response of HaCaT to UVB irradiation - Rong-Shing Chang; Chi-Shuo Chen; Ching-Lung Huang; Chiu-Ting Chang; Yujia Cui; Wei-Ju Chung; Wun-Yi Shu; Chi-Shiun Chiang; Chun-Yu Chuang; Ian C. Hsu (In Vitro Cellular & Developmental Biology - Animal, 2018)

Expression of a gene encoding a rice RING zinc-finger protein, OsRZFP34, enhances stomata opening - Kuo-Hsuan Hsu; Chia-Chin Liu; Shaw-Jye Wu; Ying-Yu Kuo; Chung-An Lu; Ching-Rong Wu; Pei-Jyun Lian; Chwan-Yang Hong; Yi-Ting Ke; Juin-Hua Huang; Ching-Hui Yeh (Plant Molecular Biology, 2014)

Toxicity and repellence of Taiwanese indigenous djulis, Chenopodium formosaneum, against Aedes albopictus (Diptera: Culicidae) and Forcipomyia taiwana (Diptera: Ceratopogonidae) - Eddie Hang Chio; En-Cheng Yang; Hsiang-Ting Huang; Err-Lieh Hsu; Chi-Rong Chen; Chin-Gi Huang; Rong-Nan Huang (Journal of Pest Science, 2013)

Identification and characterization of a novel chloroplast/mitochondria co-localized glutathione reductase 3 involved in salt stress response in rice - Tsung-Meng Wu; Wan-Rong Lin; Yun-Ting Kao; Yi-Ting Hsu; Ching-Hui Yeh; Chwan-Yang Hong; Ching Huei Kao (Plant Molecular Biology, 2013)